Experimental investigation of coherent bremsstrahlung in a mosaic pyrolytic graphite crystal; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 119, iss. 1-2 - Amosov C. Yu.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Verzilov V. A.; Vnukov I. E. (1996, 1996)
Title screen